1996
DOI: 10.1046/j.1365-2249.1996.d01-787.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced natural but diminished antibody-mediated cytotoxicity in the lungs of MRLlpr/lpr mice

Abstract: SUMMARYHuman systemic lupus erythematosus (SLE) patients, as well as MRLlpr/lpr mice which develop a SLElike disease, have decreased numbers and functional activity of systemic natural killer (NK) cells. In contrast, it has been found that among lymphocytes recovered from the bronchoalveolar lavage fluid of SLE patients, NK cells were increased in number, correlating with the severity of the lung engagement. The present study was undertaken to assay the capacity for natural killing in the lung compartment of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…The phenotypic and functional aspects of NK cells in SLE target organs have not been studied extensively. To date, only 3 studies have been published, 2 of which reported a more cytotoxic phenotype for liver and lung NK cells from diseased MRL/lpr mice than from prediseased MRL/MpJ or MRL/lpr mice [45,46]. In a 3rd study, PMA/ionomycin-stimulated NK cells from diseased MRL/lpr mice produced more cytotoxic granules than prediseased MRL/lpr or MRL/MpJ mice [10].…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic and functional aspects of NK cells in SLE target organs have not been studied extensively. To date, only 3 studies have been published, 2 of which reported a more cytotoxic phenotype for liver and lung NK cells from diseased MRL/lpr mice than from prediseased MRL/MpJ or MRL/lpr mice [45,46]. In a 3rd study, PMA/ionomycin-stimulated NK cells from diseased MRL/lpr mice produced more cytotoxic granules than prediseased MRL/lpr or MRL/MpJ mice [10].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that NK cells may be regulators of the disease state (37) and functional defects in the NK‐cell population have been identified concomitantly with defects in CD4 + CD25 + T reg from patients with insulin‐dependent diabetes mellitus (38). In contrast, NK cells in some animal models of autoimmunity may exacerbate the disease state (39–41). The contribution of CD16 + cells to the follicular infiltrate in AA has not previously been explored, and whether NK cells are systemic functional regulators or promoters of inflammation in AA is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells from liver and lungs of diseased MRL/MpJ lpr mice have enhanced natural cytotoxicity compared with healthy controls [79,80]. Long-term NK cell depletion delays glomerulonephritis onset in NZBxNZW(F1) mice [81], which suggests a local role for these cells.…”
Section: Organ-specific Differences In Sle-looking In the Right Place?mentioning
confidence: 99%